World Wide Dairy Development - At a Glance - Kalaiselvi, P.; Somasundaram, M. (Indian Journal of Marketing, 2011)
Milk is as ancient as mankind itself, as it is the substance created to feed the mammalian infant. All species of mammals, from man to whales, produce milk for this purpose. Many centuries ago, perhaps as early as 6000-8000 BC, ancient man learned to domesticate species of animals for the provision of milk to be consumed by them. These included cows, buffaloes, sheep, goats, and camels, all of which are still used in various parts of the world for the production of milk for human consumption. Fermented products such as cheese were discovered by accident, but their history has also been documented for many centuries, as has the production of concentrated milks, butter, and even ice cream. The role of milk in the traditional diet has varied greatly in different regions of the world. The tropical countries have not been traditional milk consumers, whereas, the more northern regions of the world, Europe (especially Scandinavia) and North America, have traditionally consumed far more milk and milk products in their diet. In tropical countries, where high temperatures and lack of refrigeration has led to the inability to produce and store fresh milk, milk has traditionally been preserved through means other than refrigeration, including immediate consumption of warm milk after milking, by boiling milk, or by conversion into more stable products such as fermented milks.